Examining common mental health disorders in people living with HIV on methadone maintenance therapy in Hanoi, Vietnam - Anisa Y. Mughal; Melissa Ann Stockton; Quynh Bui; Vivian Go; Brian W. Pence; Tran Viet Ha; Bradley N. Gaynes (BMC, 2021)
Abstract Background Injection drug use drives HIV transmission in Southeast Asia, where around a quarter of users are living with HIV. Vietnam developed Methadone Maintenance Therapy (MMT) programs to reduce unsafe drug abuse. Common mental health disorders (CMD), including depression, anxiety and post-traumatic stress disorder (PTSD), can worsen MMT outcomes and are highly prevalent among people living with HIV (PLH). We aimed to characterize HIV and CMD among MMT patients and assess the impact of HIV and CMD on MMT engagement outcomes in Hanoi, Vietnam. Methods This cross-sectional study was conducted at an urban MMT clinic in Hanoi. Participants were screened for CMD with the relevant sections of the Mini International Neuropsychiatric Interview (MINI). Tabular comparisons and regression models were used to understand the association of HIV and CMD with substance use and methadone compliance. Results Of the 400 MMT participants, 22% were living with HIV, 11% a CMD, 27% reported injection drug use, and 27% reported methadone noncompliance. Around 17% of those with HIV also had a CMD. Reporting non injection and injection drug use were each higher among those with CMD regardless of HIV status. In addition, reporting any drug use was much higher among those with both HIV and CMD than among those with neither (73% vs 31%, p value 0.001). While methadone noncompliance was lower among PLH than among those without HIV (16.3% vs 30.1%, p value 0.010), noncompliance was higher among those with CMD than among those without (40.5% vs 25.6%, p value 0.045). Among those without HIV, noncompliance was higher among those with CMD than among those without, but among those with HIV, the opposite relationship was observed. Conclusion There is complex overlap between substance use and methadone noncompliance among MMT patients living with HIV, CMD or both. In this population, we found a high prevalence of CMD and substance use among PLH, and a high prevalence of substance use and methadone noncompliance among those with CMD. Prioritizing provision of mental health care services to MMT patients living with HIV can help improve engagement with substance use disorder treatment and reduce the risk of HIV transmission.